2011
DOI: 10.15835/nsb315609
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Maize-Cowpea Intercropping System Related to Environmental Resources Consumption

Abstract: A field experiment was carried out in Ramhormoz, Iran during the 2008-2009 growing season to investigate the effects of different planting pattern of intercropping on environmental resource consumption and weed biomass. A randomized complete block design (RCBD) with three replications was employed to compare the treatments. Treatments included maize sole crop (M), cow pea sole crop (C), within row intercropping (I 1 ), row intercropping (I 2 ) and mix cropping (I 3 ). The density of intercropping was according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Thus, intercrop canopies can intercept PAR more effectively than sole crops. So, as concluded by Watiki et al (1993) and Eskandari and Kazemi (2011), intercropping leads to an increase in the total amount of PAR captured and PAR seem to play a relatively important role in determining total intercrop productively. As concluded by Keating and Carberry (1993), wheat and bean can differ in PAR interception because of differences in their vertical arrangement of foliage and canopy architecture and can therefore intercept more PAR compared to sole crops.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, intercrop canopies can intercept PAR more effectively than sole crops. So, as concluded by Watiki et al (1993) and Eskandari and Kazemi (2011), intercropping leads to an increase in the total amount of PAR captured and PAR seem to play a relatively important role in determining total intercrop productively. As concluded by Keating and Carberry (1993), wheat and bean can differ in PAR interception because of differences in their vertical arrangement of foliage and canopy architecture and can therefore intercept more PAR compared to sole crops.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, intercrop canopies can intercept PAR more effectively than sole crop. So, as concluded by Eskandari and Kazemi [27], intercropping are leading to increase the total amount of PAR captured and PAR seem to play a fairly important role in determining total intercrop production.…”
Section: Discussionmentioning
confidence: 79%
“…Our results are in agreement with Fernández-Aparicio et al (2007), who demonstrated that intercropping with cereals decreases infection by O. crenata in legumes, and allelochemicals released by cereal roots inhibited O. crenata seed germination. A limiting effect of intercropping on the number and biomass of weeds has been reported by a number of researchers (Carruthers et al 1998;Poggio 2005;Amanullah et al 2006;Banik et al 2006;Gharineh and Moosavi 2010;Eskandari and Kazemi 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Weed suppression in intercropping via more effective use of environmental resources by component crops has been reported in many studies (Liebman and Dyck 1993;Oleszek 1994;Mashingaizde et al 2000;Wanic et al 2004;Poggio 2005;Eskandari and Kazemi 2011). Second, intercropping may provide greater crop yield without weed suppression below levels observed in component sole cropping if intercropping uses resources which are not exploitable by weeds or convert resources to harvestable material more effectively than sole cropping systems (Liebman and Dyck 1993;Eskandari and Kazemi 2011). Parker and Riches (1993) reported that the effects of intercropping on the control of Striga is due to the fact that the intercropped non-host legumes may act as trap crops, and stimulate suicidal Striga germination.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation